Single-Cell RNA-Seq of Bone Marrow Cells in Aplastic Anemia - Tonglin, Hu; Yanna, Zhao; Xiaoling, Yu; Ruilan, Gao; Liming, Yin (Frontiers in Genetics, 2022)
Aplastic anemia (AA) is an autoimmune disease characterized by peripheral blood pancytopenia and bone marrow failure. Recently, a research study verified bone marrow failure of AA patients resulting from hematopoietic stem and progenitor cell (HSPC) attack by active T cells. Nonetheless, whether B cells, as one of the important immune cells, destruct the hematopoiesis is still unclear. Here, a large-scale single-cell transcriptomic sequencing of 20,000 bone marrow cells from AA patients and healthy donors was performed. A total of 17 clusters and differentially expressed genes were identified in each cluster relative to other clusters, which were considered potential marker genes in each cluster. The top differentially expressed genes in HSPCs (S100A8, RETN, and TNFAIP3), monocytes (CXCL8, JUN, and IL1B), and neutrophils and granulocytes (CXCL8, NFKBIA, and MT-CYB) were related to immune and inflammatory injury. Then, the B-cell receptor (BCR) diversities and pairing frequencies of V and J genes were analyzed. The highest pairing frequencies in AA patients were IGHV3-20-IGKJ2, IGHV3-20-IGKJ4, and IGHV3-20-IGHLJ2. Meanwhile, there were 3 V genes, including IGHV3-7, IGHV3-33, and IGLV2-11, with elevated expression in B cells from AA patients. Cell type–specific ligand–receptor was further identified in B-cell interaction with hematopoietic cells in the bone marrow. The changed ligand–receptor pairs involved antigen presentation, inflammation, apoptosis, and proliferation of B cells. These data showed the transcriptomic landscape of hematopoiesis in AA at single-cell resolution, providing new insights into hematopoiesis failure related with aberrance of B cells, and provide available targets of treatment for AA.